Factors affecting the supply of urban regulating ecosystem services. Empirical estimates from Cagliari, Italy - Lai, Sabrina; Zoppi, Corrado (TeMA - Journal of Land Use, Mobility and Environment, 2023)
This study aims at analyzing the relationships between supply of ecosystem services, features of green areas and characteristics of settlements in urban contexts, by taking the Italian city of Cagliari as study area. The services offered by the urban ecosystems that are identified as the most relevant in association with the spatial framework of green areas in urban environments are heat mitigation, carbon capture and storage, and runoff control, with particular reference to flood-related events. The features of green areas are identified with reference to the height of vegetation, by distinguishing between grasslands, shrubby cover, and trees and woodland cover. Finally, we characterize the urban settlement through the building and population densities, and through the education level, as a proxy for the residents’ social statuses. The assessment of performances of the urban ecosystem services shows negative correlations with the intensity of urbanization, whereas the size of the enhancement in the supply of ecosystem services can be associated with different types of green areas. In terms of policy implications, the outcomes of the study show that there is plenty of room for improvement in the ecosystem services performance based on fine-tuning measures which involve building and population densities and vegetation cover.